Carbon Nanotubes: Promoting the Water Oxidation Catalysis by Synergistic Interactions between Ni(OH)2 and Carbon Nanotubes (Adv. Energy Mater. 15/2016). Issue 15 (10th August 2016) - Wang, Lei; Chen, Hong; Daniel, Quentin; Duan, Lele; Philippe, Bertrand; Yang, Yi; Rensmo, Håkan; Sun, Licheng
Abstract : In article number 1600516, Licheng Sun and co‐workers describe a clean and renewable energy system: highly efficient hybrid water oxidation catalyst based on carbon nanotubes and Ni(OH)2 nano‐plates. The image shows the work towards a highly efficient hybrid catalyst for water oxidation. By using this hybrid catalyst, water molecules can be efficiently oxidized to generate oxygen bubbles.